Abidjan, Metropole Nationale Et Internationale - Yao YAO, Mathieu; David BRENOUM , Kouakou; Koffi ATTA, Lazare (International Journal of Scientific Research and Management (IJSRM), 2022)
Abidjan is a city that has known an exceptional destiny. It has known thanks to its port, an extraordinary development polarizing a vast demographic pool which goes beyond national borders. This rapid and continuous development from 1950 resulted from an influx of migrants, a large proportion of whom were foreigners. The engine of the spatial expansion of the city was above all the effort to create equipment and port and industrial spaces. Everything is done to make Abidjan a growth pole and a reflection of Ivorian urbanization. It has become in less than a century a great African metropolis, which is growing year after year. This article aims to show the features of the Abidjan metropolis. To achieve this, first-hand observation and documentary research were carried out. It emerges from this analysis that the centralization of trade and administration in this city and the shortcomings of the distribution system in the interior of the country confirm the industrialists in the idea that the Ivorian capital remains the best place for investment. This overwhelming primacy over others at all levels leads to rapid demographic and spatial growth. Today, Abidjan is a megacity due to its size, extent and population. It currently has nearly 5 million inhabitants (RGPH, 2014). With its 70,000 ha, it is five times larger than Paris, capital of France and the largest French-speaking city in West Africa (Chenal, 2009, p.114).